KAJIAN PERUBAHAN JERAPAN DAN KETERSEDIAAN P PADA TANAH ULTISOL DENGAN PEMBERIAN LIMBAH KELAPA SAWIT (Fakultas Pertanian Universitas Palangka Raya, 2017)
The purpose of this research is to know the influence of the incorporation TKKS and boiler ashes best doses in lowering adsorption P and increase the availability of P and pH on Ultisols. This study used a Randomized Complete Design (RAL) consisting of 2 factorial factor treatments. First factor was TKKS (T) consists of three doses of treatment i.e: T0 : 0 ton.ha?1, T1 : 20 ton.ha?1 dan T2 : 40 ton.ha?1. Second Factor was Boiler Ash (A) consists of three doses of treatment i.e: A0 : 0 ton.ha?1, A1 : 11,6 ton.ha?1 dan A2 : 23,2 ton.ha?1. The results showed that combination treatment of empty oil palm bunches (TKKS) and boiler ashes on ultisols has raised pH H2O, raised and lowered ?pH when the dose increased, and lowered exchangeable Al. Whereas single TKKS factor treatment and boiler ash raise pH KCl. Single factor Treatment of boiler ash increases P-available with the best dose treatment i.e. A2 (23,2 ton ha-1), it also increases the coefficient of bonding energy and lowering the site adsorption namely treatment A1 (11,6 ton.ha-1) and A2 (23,2 ton.ha-1), while the single factor treatment of TKKS improves P adsorption maximum i.e. treatment T1 (20 ton.ha-1), but lose the P adsorption maximum i.e. treatment T2 (40 ton.ha-1)